Проблема кримінальної відповідальності за дифамацію в професійній діяльності журналістів - Пахнін, М. Л.; Pakhnin, M. L.; Микола Пахнін (Наше право. - 2021. - № 4. - С. 83-88, 2021)
Вивчено необхідність та доцільність впровадження в національне законодавство кримінально-правових норм про наклеп та образу (дифамацію) та їх вплив на свободу слова та журналістську діяльність. Проведено порівняльно-правовий аналіз кримінальних законів зарубіжних країн щодо кримінальної відповідальності за вказані дії.

The necessity and expediency of introduction into national legislation of criminal law norms on defamation and defamation and their impact on freedom of speech and journalism are studied. The author conducted a comparative legal analysis of the criminal laws of foreign countries on criminal liability for these actions. It is established that almost every European country, as well as a significant number of CIS countries has rules on criminal liability for defamation (in its various variations). The arguments of both opponents and supporters of the introduction of a criminal law ban on defamation are investigated. It is concluded that it is possible to introduce liability for defamation and insult as an exceptional preventive measure to influence the violator in case of intentional dissemination of knowingly false information.

Изучена необходимость и целесообразность внедрения в национальное законодательство уголовно-правовых норм о клевете и оскорблении (диффамации) и их влиянии на свободу слова и журналистскую деятельность. Проведен сравнительно-правовой анализ уголовных законов зарубежных стран по уголовной ответственности за указанные действия.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; журналістська діяльність; journalistic activity; журналистская деятельность; дифамація; defamation; диффамация; наклеп; slander; клевета; образа; insult; оскорбление; кримінальна відповідальність; criminal liability; уголовная ответственность; свобода слова; freedom of speech; зарубіжний досвід; foreign experience; зарубежный опыт; законодавство; legislation; законодательство